2002 ANTIMONOPOLY AND FAIR COMPETITION LAW NO. 5/1999: CARTEL AND MERGER CONTROL IN INDONESIA: - - Rachbini, Didik J (jurnalhukumbisnis.com, 2016)
Antimonopoly and Fair Competition Law No. 5/1999: Cartel and Merger Control in Indonesia